Lucky for good - Patron, Susan 1948- (Listening Library, Random House Audio Publishing Group, 2011)
The residents of Hard Pan, California, come together to help Brigitte and Lucky when the County Health Department threatens to close down the café, and meantime Miles's life is complicated by his mother's return. Third book in the Hard Pan trilogy, featuring Lucky Trimble
Final story in Lucky's hard pan trilogy.
Empfohlen für Hörer von 9 bis 12 Jahren
Keywords: Restaurants / Juvenile fiction; Interpersonal relations / Juvenile fiction; Community life / California / Juvenile fiction; Mothers and sons / Juvenile fiction; Christian life / Juvenile fiction; California / Juvenile fiction; Christian life; Community life; Interpersonal relations; Mothers and sons; Restaurants; California; Audiobooks; Children's audiobooks; Fiction; Juvenile works; Hörbuch; Kinderbuch; CD